A manikin or human simulator—development of a tool for measuring students’ perception - Torres,Kamil; Evans,Phillip; Mamcarz,Izabela; Radczuk,Natalia; Torres,Anna (PeerJ, 2022)
Background Education with the use of medical simulation may involve the use of two modalities: manikins or standardized patients (SPs) to meet specific learning objectives. We have collected students’ opinions about the two modalities which can be helpful in planning and evaluating the curriculum process. Although reviews or comparisons of student opinions appear in the literature, it is difficult to find a scale that would be based on a comparison of specific effects that can be obtained in the educational process. In order to fill this gap, an attempt was made to construct a questionnaire. Methods An experimental version of a questionnaire measuring the final-year students’ (273) opinions about the effectiveness of both simulation techniques has been designed on the basis of semi-structured interviews. They were conducted with 14 final-year students excluded from the subsequently analyzed cohort. The scale has been completed, tested and validated. Results The authors developed a 33-statement questionnaire which contain two scales: teaching medicine with the manikins and with the SPs. Two factors were identified for each scale: Doctor-patient relationship and practical aspects. The scales can be used complementary or separately, as the article reports independent statistics for each scale. The Cronbach’s alpha coefficient for the manikin scale is 0.721 and for the SP scale is 0.758. Conclusions The questionnaire may be applied to medical students to identify their opinions about using manikins and SPs in teaching. It may have an important impact for planning curriculum and implementing particular modalities in accordance with the intended learning objectives.
Keywords: Medical education; Simulation environment; Undergraduate students; Curriculum design; Standardized patient; Manikin